Klinefelter Syndrome – Etiology, Clinical Presentation and Modern Approaches to the Diagnosis and Treatment: A Literature Review - Kupczyk, Katarzyna; Kazachok, Mikhail; Paruszewski, Szymon; Dybcio, Aleksandra; Jońca, Mikołaj; Kurys, Natasza; Szydłowska, Dorota; Kubisa, Adam; Miluski, Mateusz; Kupczak, Julia (Journal of Education, Health and Sport, 2026)
Introduction: Klinefelter syndrome is the most common chromosomal abnormality in males, characterized by the presence of an extra X chromosome, resulting in 47, XXY karyotype. Its prevalence is approximately 1 in 500 to 1 in 1,000 live-born males. The phenotypic expression is highly variable and includes hypogonadism, infertility, and an increased risk of metabolic complications and neurocognitive disorders. Purpose: The aim of this review is to provide a comprehensive synthesis of the current state of knowledge on Klinefelter syndrome, with particular emphasis on modern diagnostic and therapeutic approaches. Material and methods: This article is a narrative literature review and was conducted using international databases. Publications were selected based on their scientific value, relevance, and relation to the topic. Results: Current evidence indicates that patients benefit from an interdisciplinary approach, involving coordinated care among multiple specialists, including andrologists, endocrinologists, geneticists, psychologists, and experts in infertility treatment. Despite its relatively high prevalence, a significant proportion of affected individuals remain undiagnosed until adulthood, resulting in delayed initiation of therapeutic interventions. Conclusions: Klinefelter syndrome is a genetic condition with numerous somatic, reproductive, and psychosocial consequences. Early diagnosis, individualized therapeutic strategies, and multidisciplinary care significantly improve long-term prognosis and quality of life in patients. Future research should prioritize the refinement of diagnostic approaches, elucidation of the long-term effects of hormone therapy, and investigation of the molecular mechanisms underlying phenotypic variability.